2010
DOI: 10.1038/nature09248
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for stone-tool-assisted consumption of animal tissues before 3.39 million years ago at Dikika, Ethiopia

Abstract: The oldest direct evidence of stone tool manufacture comes from Gona (Ethiopia) and dates to between 2.6 and 2.5 million years (Myr) ago. At the nearby Bouri site several cut-marked bones also show stone tool use approximately 2.5 Myr ago. Here we report stone-tool-inflicted marks on bones found during recent survey work in Dikika, Ethiopia, a research area close to Gona and Bouri. On the basis of low-power microscopic and environmental scanning electron microscope observations, these bones show unambiguous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
340
1
13

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 600 publications
(358 citation statements)
references
References 25 publications
4
340
1
13
Order By: Relevance
“…The oldest stone tools found so far are dated to 2·6 Mya (258,259) and it has been suggested that these were used for flesh removal and percussion on long bones for marrow access. From this time onward stone tools were apparently used for defleshing and butchering of large animals.…”
Section: Archeologymentioning
confidence: 99%
“…The oldest stone tools found so far are dated to 2·6 Mya (258,259) and it has been suggested that these were used for flesh removal and percussion on long bones for marrow access. From this time onward stone tools were apparently used for defleshing and butchering of large animals.…”
Section: Archeologymentioning
confidence: 99%
“…With H. erectus, there is an increase in body size, skeletal indicators of a striding bipedal gait, a reduction in the size of the teeth and jaws and a substantial jump in relative brain size, which together with the evidence from the archaeological record suggest a dietary strategy that included bulk processing of a significant proportion of high-quality, calorie-rich food items [6,28,36 -38] (figure 1). There is evidence at this time for extraction of marrow and flesh from large mammals using stone tools [39 -41], although recent evidence argues that this may have occurred much earlier in Australopithecus afarensis [42]. Early representatives of the genus Homo probably used tools for the processing of both animal and plant materials and for wooden tool production [36,43]; however, hunting weapons do not show up unequivocally in the fossil record until about 400 thousand years ago [44].…”
Section: The Importance Of Metabolic Changes During Human Evolutionmentioning
confidence: 99%
“…The earliest direct archaeological evidence of food item processing using Oldowan stone tools is from animal bones, which show cut marks associated with stripping off edible soft tissue and also fractures associated with cracking them open to obtain edible bone marrow. Using stone tools to cut animal soft tissue is attested from marks on the surfaces of bones in the earliest archaeological record (2.5 -2.6 Myr BP, associated with the extinct hominin Australopithecus garhi [24]; possibly also at 3.4 Myr BP and associated with Australopithecus afarensis [3], but see [25]). …”
Section: Introductionmentioning
confidence: 99%
“…Archaeological evidence suggests that tool use has been fundamental to hominin life for at least 2.6 Myr [1,2] and probably more [3,4]. Stone knapping represents the earliest known instance of toolmaking and tool use by early hominins [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%